Evaluating strategies to enhance traffic safety - Albrecht, James F. (Critical issues and global perspectives ; volume 1: Special topics in policing, 2024)
Global industrialization brought population expansion and eventually the need for personal and mass transportation. The twentieth century saw the development of the motor vehicle, which replaced the horse and the train as the primary options for public mobility. As the use of motor vehicles has expanded across time and the world, so too has the inherent dangers to the public. While there are clear benefits to this means of mass transportation, approximately 1.25 million people die in vehicle crashes globally each year. The three primary contributing factors to these vehicular crashes include excessive speed, driving while intoxicated, and the absence of safety devices including seat belts and helmets (when traveling via motorcycle). Since the invention of motor vehicles, “drink driving” has been a concern to society. Alcohol is involved in approximately 22% of all traffic fatalities globally for a total of 273,000 deaths annually. In the USA, more than 10,000 people lose their lives to drink driving each year, i.e., more than 30 people die per day. There is therefore a strong need to enhance traffic safety in an effort to reduce vehicle accidents and related injuries and fatalities. Measures to prevent incidents involving driving while intoxicated and prevent vehicle crashes will be highlighted within this chapter.